Parallel association of shunt active power filters - Pregitzer, Ricardo G. (2007)
This paper describes different types of parallel association of Shunt Active Power Filters, presents computer simulation models developed in PSCAD/EMTDC, and shows simulated results for each case. The control system used in the active filters is based on the Instantaneous Reactive Power Theory (p-q Theory). The active filters use periodic sampling as switching technique. Two types of parallel associations are presented: two active filters in different parallel feeders; and both active filters connected in parallel at the same point of the electric installation. The paper also proposes a control strategy to solve an inherent operation problem that occurs in the second type of parallel association.